Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Continent‐Wide Drivers of Spatial Synchrony in Breeding Demographic Structure Across Wild Great Tit Populations - Joe P. Woodman; Stefan J. G. Vriend; Frank Adriaensen; Elena Álvarez; Alexander Artemyev; Emilio Barba; Malcolm D. Burgess; Samuel P. Caro; Laure Cauchard; Anne Charmantier; Ella F. Cole; Niels Dingemanse; et al. (Ecology Letters, 2025)
Variation in age structure influences population dynamics, yet we have limited understanding of the spatial scale at which its fluctuations are synchronised between populations. Using 32 great tit populations, spanning 4° W–33° E and 35°–65° N involving > 130,000 birds across 67 years, we quantify spatial synchrony in breeding demographic structure (subadult vs. adult breeders) and its drivers. We show that larger clutch sizes, colder winters, and larger beech crops lead to younger populations. We report distance‐dependent synchrony of demographic structure, maintained at approximately 650 km. Despite covariation with demographic structure, we do not find evidence for environmental variables influencing the scale of synchrony, except for beech masting. We suggest that local ecological and density‐dependent dynamics impact how environmental variation interacts with demographic structure, influencing estimates of the environment's effect on synchrony. Our analyses demonstrate the operation of synchrony in demographic structure over large scales, with implications for age‐dependent demography in populations.

Oyster-inspired carbon dots-functionalized silica and dialdehyde chitosan to fabricate a soy protein adhesive with high strength, mildew resistance, and long-term water resistance - Shiqing Chen; Xinyi Li; Mingyang Bai; Sheldon Q. Shi; John Tosin Aladejana; Jinfeng Cao; Jianzhang Li (Carbohydrate Polymers, 2023)

Temporal patterns and causal drivers of aboveground plant biomass in a coastal wetland: Insights from time-series analyses - Kadir Biçe; John Schalles; Joan E. Sheldon; Merryl Alber; Christof Meile (Frontiers in Marine Science, 2023)
Salt marshes play a crucial role in coastal biogeochemical cycles and provide unique ecosystem services. Salt marsh biomass, which can strongly influence such services, varies over time in response to hydrologic conditions and other environmental drivers. We used gap-filled monthly observations of Spartina alterniflora aboveground biomass derived from Landsat 5 and Landsat 8 satellite imagery from 1984-2018 to analyze temporal patterns in biomass in comparison to air temperature, precipitation, river discharge, nutrient input, sea level, and drought index for a southeastern US salt marsh. Wavelet analysis and ensemble empirical mode decomposition identified month to multi-year periodicities in both plant biomass and environmental drivers. Wavelet coherence detected cross-correlations between annual biomass cycles and precipitation, temperature, river discharge, nutrient concentrations (NO x and PO 4 3– ) and sea level. At longer periods we detected coherence between biomass and all variables except precipitation. Through empirical dynamic modeling we showed that temperature, river discharge, drought, sea level, and river nutrient concentrations were causally connected to salt marsh biomass and exceeded the confounding effect of seasonality. This study demonstrated the insights into biomass dynamics and causal connections that can be gained through the analysis of long-term data.

Temperature synchronizes temporal variation in laying dates across European hole‐nesting passerines - Stefan J. G. Vriend; Vidar Grøtan; Marlène Gamelon; Frank Adriaensen; Markus P. Ahola; Elena Álvarez; Liam D. Bailey; Emilio Barba; Jean‐Charles Bouvier; Malcolm D. Burgess; Andrey Bushuev; Carlos Camacho; et al. (Ecology, 2023)
Identifying the environmental drivers of variation in fitness‐related traits is a central objective in ecology and evolutionary biology. Temporal fluctuations of these environmental drivers are often synchronized at large spatial scales. Yet, whether synchronous environmental conditions can generate spatial synchrony in fitness‐related trait values (i.e., correlated temporal trait fluctuations across populations) is poorly understood. Using data from long‐term monitored populations of blue tits ( Cyanistes caeruleus , n = 31), great tits ( Parus major , n = 35), and pied flycatchers ( Ficedula hypoleuca , n = 20) across Europe, we assessed the influence of two local climatic variables (mean temperature and mean precipitation in February–May) on spatial synchrony in three fitness‐related traits: laying date, clutch size, and fledgling number. We found a high degree of spatial synchrony in laying date but a lower degree in clutch size and fledgling number for each species. Temperature strongly influenced spatial synchrony in laying date for resident blue tits and great tits but not for migratory pied flycatchers. This is a relevant finding in the context of environmental impacts on populations because spatial synchrony in fitness‐related trait values among populations may influence fluctuations in vital rates or population abundances. If environmentally induced spatial synchrony in fitness‐related traits increases the spatial synchrony in vital rates or population abundances, this will ultimately increase the risk of extinction for populations and species. Assessing how environmental conditions influence spatiotemporal variation in trait values improves our mechanistic understanding of environmental impacts on populations.

Caldera-like features located over the Panikkar Seamount and adjacent regions in the Laxmi Basin, eastern Arabian Sea - J John Savio; V Yatheesh; R Sheldon; M Kallathian; Pratima Kessarkar; Kuldeep Kumar; P Mahesh; Subhashree Mishra; Swati Verma (Journal of Earth System Science, 2022)

The Glycocalyx and Its Role in Vascular Physiology and Vascular Related Diseases - Sheldon Weinbaum; Limary M. Cancel; Bingmei M. Fu; John M. Tarbell (Cardiovascular Engineering and Technology, 2021)

Sediment excavation as a wetland restoration technique had early effects on the developing vegetation community - Danelle M. Larson; John Riens; Sheldon Myerchin; Shawn Papon; Melinda G. Knutson; Sara C. Vacek; Sarah G. Winikoff; Mindy L. Phillips; John H. Giudice (Wetlands Ecology and Management, 2020)

Long-term T-DNA insert stability and transgene expression consistency in field propagated sugarcane - Kerry Hosmer Caffall; Chengkun He; Michele Smith-Jones; Kristin Mayo; Pearl Mai; Shujie Dong; John Ke; Erik Dunder; Michele Yarnall; Rachel Whinna; Joe DeMaio; Weining Gu; et al. (Plant Molecular Biology, 2017)

Replicated analysis of the genetic architecture of quantitative traits in two wild great tit populations - Anna W. Santure; Jocelyn Poissant; Isabelle De Cauwer; Kees van Oers; Matthew R. Robinson; John L. Quinn; Martien A. M. Groenen; Marcel E. Visser; Ben C. Sheldon; Jon Slate (Molecular Ecology, 2015)
Currently, there is much debate on the genetic architecture of quantitative traits in wild populations. Is trait variation influenced by many genes of small effect or by a few genes of major effect? Where is additive genetic variation located in the genome? Do the same loci cause similar phenotypic variation in different populations? Great tits ( Parus major ) have been studied extensively in long‐term studies across Europe and consequently are considered an ecological ‘model organism’. Recently, genomic resources have been developed for the great tit, including a custom SNP chip and genetic linkage map. In this study, we used a suite of approaches to investigate the genetic architecture of eight quantitative traits in two long‐term study populations of great tits—one in the Netherlands and the other in the United Kingdom. Overall, we found little evidence for the presence of genes of large effects in either population. Instead, traits appeared to be influenced by many genes of small effect, with conservative estimates of the number of contributing loci ranging from 31 to 310. Despite concordance between population‐specific heritabilities, we found no evidence for the presence of loci having similar effects in both populations. While population‐specific genetic architectures are possible, an undetected shared architecture cannot be rejected because of limited power to map loci of small and moderate effects. This study is one of few examples of genetic architecture analysis in replicated wild populations and highlights some of the challenges and limitations researchers will face when attempting similar molecular quantitative genetic studies in free‐living populations.

The Holocene History of Nares Strait: Transition from Glacial Bay to Arctic-Atlantic Throughflow - Anne Jennings; Christina Sheldon; Thomas Cronin; Pierre Francus; Joseph Stoner; John Andrews (Oceanography, 2011)

Synthesis and pharmacological evaluation of m-terphenyl amines as cyclooxygenase inhibitors - John D. Bauer; Michael S. Foster; Jeffrey D. Hugdahl; Kristi L. Burns; Sheldon W. May; Stanley H. Pollock; Horace G. Cutler; Stephen J. Cutler (Medicinal Chemistry Research, 2007)

Defining the expression pattern of the LGI1 gene in BAC transgenic mice - Karen Head; Shiaoching Gong; Sheldon Joseph; Cuidong Wang; Tania Burkhardt; Michael R. Rossi; Jeffrey LaDuca; Sei-Ichi Matsui; Mary Vaughan; David G. Hicks; Nathaniel Heintz; John K. Cowell (Mammalian Genome, 2007)

Wind environment in the Lee of Kauai Island, Hawaii during trade wind conditions: weather setting for the Helios Mishap - John N. Porter; Duane Stevens; Kevin Roe; Sheldon Kono; David Kress; Eric Lau (Boundary-Layer Meteorology, 2007)

Cellular Fluid Mechanics and Mechanotransduction - John M. Tarbell; Sheldon Weinbaum; Roger D. Kamm (Annals of Biomedical Engineering, 2005)

Concurrent measurements of the free cytosolic concentrations of H+ and Na+ ions with fluorescent indicators - Claire Sheldon; Y.May Cheng; John Church (Pflügers Archiv - European Journal of Physiology, 2004)

Population Genetic Structure of Earthworms (Lumbricus rubellus) in Soils Contaminated by Heavy Metals - John D. Peles; William I. Towler; Sheldon I. Guttman (Ecotoxicology, 2003)

The identical 5? splice-site acceptor mutation in five attenuated APC families from Newfoundland demonstrates a founder effect - Lisa Spirio; Jane Green; Jennifer Robertson; Margaret Robertson; Brith Otterud; John Sheldon; Erica Howse; Roger Green; Ray White; Mark Leppert; Joanna Groden (Human Genetics, 2000)

Identification and genetic control of two rabbit low-density lipoprotein allotypes - John J. Albers; Sheldon Dray (Biochemical Genetics, 1968)